Cloning and characterization of the NAC-like gene NAC2 in Arachis hypogaea L. - Thu Nga, Nguyen Thi; Son, Le Van; Binh, Le Tran; Mai Anh, Banh Thi (Academia Journal of Biology, 2013)
NAC proteins are plant-specific transcription factors and more than 100 NAC genes have been identified in Arabidopsis and rice to date. NAC transcription factors exist differentially in plant and are the new transcription regulatory factors with multiple biological functions. NAC transcription factors have a variety of important functions not only in plant development but also in abiotic stress responses. Stress-inducible NAC genes have been shown to be involved in abiotic stress tolerance. In this paper, the results on cloning and characterization of NAC2 gene from L12 peanut cultivar are presented. NAC2 gene cloning by RT-PCR, including an open reading frame with 1050 bp encoding 349 amino acids. Sequencing analysis showed that the deduced protein of NAC2 including the conservative NAC domains (The NAC domain can be subdivided into five subdomains (A to E)) have characteristic features of the NAC transcription factors. When comparing the amino acid sequence in NAC domain of NAC2 and AhNAC2 genes two amino acid changes were found at position 78 and 115. However, when comparing the amino acid sequence in the conservative region of the NAC2 gene with that of other plants such as soybean, rice, and Arabidopsis thaliana, no change was found at position 115 (amino acid K); there was only one change in position 78. A high of similarity when comparing the deduced amino acid sequence of the NAC2 gene with those of NAC transcription factors in other plant species (closest gene NAC4 in soybean - GmNAC4). Many studies have shown the key role of NAC2 in response to the stimulus signal from the ABA and drought resistance of peanut. NAC2 gene sequence has been registered on the Genbank with the accession number HF546358. The results of this study will be used in construction transformation vector carrying NAC2 transcription factor to improve the drought tolerance of peanut.